Military woman and defense policy: reflections from Ecuador and Buen Vivir - Daniel Valdivieso, Cristian [UNESP] (Univ Autonoma Madrid, 2022)
Since 2007, after the election of the economist Rafael Correa Delgado for president of the Republic of Ecuador, the country has been experiencing a series of ideological, structural and political changes. A Constitutional Assembly, demanded by a Popular Consultation, materialized Correa's project of homeland refoundation (Ulloa, 2020, p. 19). In 2008, once the Constitution had been drafted, 63,93% of the voting population said Yes to the new Constitution, thus establishing what would be a turning point in national politics. On the one hand, until the fall of Colonel Lucio Gutierrez (2003-2005), the country had undergone turbulence during the nineties due to significant political-institutional instability. There were three political leaders toppled in total; an armed conflict with its neighbor country, Peru; and a deep economic crisis that led the country to embark on dollarization. Correa's presidency, on the other hand, lasted ten years (2007-2017), after which time he left one of his vice-presidents Lenin Moreno as successor (2017-2021). In addition, despite the corruption during his government, he continues to lead the second largest political party, as can be seen in the 2021 elections. His Plan of Government, called 'Plan Nacional para el Buen Vivir,' introduced the indigenous worldview of Sumak Kawsay. Translated from quichua language as Buen Vivir, this philosophy enabled the adoption of social inclusion measures, the enlargement of minority rights, including the expansion of the liberal juridical anthropocentric concept, by offering nature rights (Hernandez, 2017). Sumak Kawsay means life in its fullness [...] in its material and spiritual excellence [...] in its inner and outer balance of the community (Macas, 2010, p. 14). Based on this philosophy, Ecuador started moving towards social change, which was impossible without the inclusion of gender equality (Zaragocin, 2017, p. 64). In that sense, many public policies have been planned, creating debates on economic, political and social issues (Acosta, 2012;Acosta y Cajas-Guijarro, 2018; Hernandez, 2017; Radcliffe, 2017). Furthermore, these policies targeted one of the most hermetic institutions: the Armed Forces. In this respect, this paper aims to analyze the discursive reproductions and disruptions in gender categories (masculine and feminine) based on an analysis of Ecuadorian defense documents. The masculinities constitute a gender category that reflects the subjugation of the feminine by the masculine, and is connected to a superiority associated with strength, rationality, command, in opposition to feminine values (weakness, emotionality, anarchy) (Hooper, 1999). Nevertheless, masculinities are not personal characteristics concerning individuals. Instead, they should be understood as configurations produced by social actions in a particular context (Connell y Messerschmidt, 2005, p. 832). In this paper, Maya Eichler's militarized masculinities (MM) concept is used as a reference to the stereotypical masculine characteristics created by the exacerbation of virility in military rituals (military service, combat) (Eichler, 2014, pp. 83-85). The author highlights that the MM are regularly and dynamically produced, making necessary an analysis on its features. Therefore, it is used to identify discursive and ideological formations and interdiscourses associated with gender notions present in the documents through a post-structural feminist approach and a discourse analysis methodology. Gender equality constitutes an unavoidable issue in contemporary democracies and consequently the inclusion of women in the Ecuadorian Armed Forces is an ongoing challenge. Recent studies on the integration of women in the military demonstrate that public policies, mainly regarding gender equality and interculturality, have been militarized (Zaragocin, 2018, p. 436). In other words, the potential for social change has been lost. From this fact, this paper argues that the militarization of gender equality, besides undermining the transformative potential of social inclusion, allowed the reproduction of new manifestations of militarized masculinities in the defense documents, updating the dynamics based on a dialectic and negative masculine/feminine dichotomy. Furthermore, the existence of a gap in the Ecuadorian security and defense literature is identified; despite the increase of women in the military, studies on this phenomenon remain incipient (Chacon, 2014; Iturralde, 2015; Morales et al., 2017; Zaldumbide, 2020; Zaragocin, 2018). Issues concerning military masculinities, hegemonic masculinity in these places and in Ecuadorian society -and their discursive reproductions, continuities and resistances- constitute a fertile ground for the analysis of the consequences of militarization for social inclusion. This paper fills this gap by analyzing the transformation in militarized masculinities in national defense discourse, and it does so through innovative methodological resources that allow a critical perspective on the results of the policies implemented since 2007. In terms of methodology, a framework of analisis is used consisting of defense documents published from 2002 to 2017, namely: Libro Blanco de Defensa (2002, 2006), Agenda Politica de Defensa (2009-2013 and 2014-2017), Politica de Genero de las Fuerzas Armadas del Ecuador (2013) and the Cartilla de Genero Fuerzas Armadas del Ecuador (2017). This framework refers to the year of 2002 due to the release of the first Libro Blanco during Gustavo Noboa's administration (2000-2003). This permits us to determine to what extent the inclusion of gender politics was an unavoidable issue in national defense politics during the documents' transition. The body of analysis is addressed through the combination of a discourse analysis and a post-structural feminist perspective on gender, using Laura Shepherd's theoretical lens. The connection between these methodologies permits the identification of the ways that gender manifests itself as an element of power in discourses. It is highlighted how the post-structural feminist perspective allows us to question how the texts signify, enabling the realization of profound analyses that address the documents' discursive meanings (Shepherd, 2010, p. 9). Discourse should be understood as word in motion, whose purpose is the production of effects of meaning (Orlandi, 2012, p. 15). Discourse is represented by oral and written word, and symbols that dispute meanings in subjective and ideological fields (Brandao, 2012, p. 9). For this study, the texts that form the body of analysis are considered discourses. In this way, discourses are understood as neither transparent nor inert (Orlandi, 2012, p. 15), but dynamic and contingent. Besides the introduction and the final considerations, the work has three sections. The first section presents the conceptual tools that will be used to understand the relation between gender and masculinities. After that, a brief description of the methodology employed in the study is developed. Finally, the analysis is conducted on the manifestations of militarized masculinities in the documents. The work finishes by presenting a final argument, that is: besides undermining the transformative potential of social inclusion, the militarization of gender equality allows for the reproduction of new manifestations of militarized masculinities in the defense documents. The dynamics are updated based on a dialectic and negative masculine/feminine dichotomy. Through this analysis three illustrative images of women's presence in the defense documents were created: partial citizen, authorized citizen and military woman. The three representations show, in a before and after comparison of gender politics, that women continue experiencing rejection in military spaces, being the Other, and inherently a stranger to the ideal of militarized masculinity that prevails in the barracks. The conclusion is that militarized masculinities have experienced a discursive metamorphosis, demonstrating the subtle and resistant armor of the masculine military ethos.
Keywords: Ecuador; militarized masculinities; defense documents; Sumak Kawsay; gender